Viskozno dušene prečne vibracije osno gibajoče se strune - Jakšić, Nikola (Strojniški vestnik, 2005)
In this paper the linear viscous-damping mechanism acting on an axially-movingstring is analyzed. The analyzed damping model is in the form . The equation of motion, i.e., the linear partial differential equation, of thefree, transverse vibrations of the stringćs span is solved first. Then the influence of the coefficients b1 and b2 on the natural frequencies and the free responses is studied. It was found that the values of the coefficients should be carefully selected in order to avoid physically unrealistic responses.
Keywords: enačbe diferencialne; enačbe hiperbolične; nihanja dušena; strune gibajoče; nihanje; dušenje; matematična analiza